2008
DOI: 10.2310/7750.2008.07036
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Management of Generalized Pustular Psoriasis with Infliximab: Case Series

Abstract: Infliximab may be efficacious for some patients for the long-term management of GPP. Maintaining a strict infliximab infusion schedule and concomitant methotrexate therapy may decrease infusion reactions and increase efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 26 publications
1
20
0
Order By: Relevance
“…These include etanercept and cyclosporine, infliximab and methotrexate, and infliximab followed by etanercept. 19,[32][33][34]43,45 Combination therapy allows physicians to maximize benefits and reduce adverse effects associated with various therapies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These include etanercept and cyclosporine, infliximab and methotrexate, and infliximab followed by etanercept. 19,[32][33][34]43,45 Combination therapy allows physicians to maximize benefits and reduce adverse effects associated with various therapies.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21][32][33][34][41][42][43] Because of the faster onset of action with infliximab and cyclosporine, many physicians consider these drugs as firstline treatment in patients with severe, acute disease.…”
Section: Discussionmentioning
confidence: 99%
“…Infliximab is highly effective, resulting in 75% clearance of psoriasis (Psoriasis Area and Severity Index (PASI) 75) in .70% patients at 12 weeks [83]. In addition to improving the chronic plaque form of the disease, infliximab has been shown to be of utility in generalised pustular psoriasis in small case series [84], although palmar plantar pustular psoriasis does not appear to respond and may even be precipitated by TNF antagonist therapy [85]. Improvement of nail disease has been demonstrated [86].…”
Section: Psoriasismentioning
confidence: 99%
“…[49] It is usually administered every 6 weeks in a dose of 5 mg/kg. Routhouska et al [50] reported success with the addition of weekly, low dose methotrexate. This is echoed by the author's experience of two generalized pustular psoriaisis patients who showed remarkable clinical improvement within 48 h of the first infusion and concomitant methotrexate 5 mg/week.…”
Section: Infliximab With Concomitant Methotrexatementioning
confidence: 97%